Deep-branching ANME-1c archaea grow at the upper temperature limit of anaerobic oxidation of methane - Benito Merino, David; Zehnle, Hanna; Teske, Andreas; Wegener, Gunter (Frontiers in Microbiology, 2022)
In seafloor sediments, the anaerobic oxidation of methane (AOM) consumes most of the methane formed in anoxic layers, preventing this greenhouse gas from reaching the water column and finally the atmosphere. AOM is performed by syntrophic consortia of specific anaerobic methane-oxidizing archaea (ANME) and sulfate-reducing bacteria (SRB). Cultures with diverse AOM partners exist at temperatures between 12 and 60 °C. Here, from hydrothermally heated sediments of the Guaymas Basin, we cultured deep-branching ANME-1c that grow in syntrophic consortia with Thermodesulfobacteria at 70 °C. Like all ANME, ANME-1c oxidize methane using the methanogenesis pathway in reverse. As an uncommon feature, ANME-1c encode a nickel-iron hydrogenase. This hydrogenase has low expression during AOM and the partner Thermodesulfobacteria lack hydrogen-consuming hydrogenases. Therefore, it is unlikely that the partners exchange hydrogen during AOM. ANME-1c also does not consume hydrogen for methane formation, disputing a recent hypothesis on facultative methanogenesis We hypothesize that the ANME-1c hydrogenase might have been present in the common ancestor of ANME-1 but lost its central metabolic function in ANME-1c archaea. For potential direct interspecies electron transfer (DIET), both partners encode and express genes coding for extracellular appendages and multiheme cytochromes. Thermodesulfobacteria encode and express an extracellular pentaheme cytochrome with high similarity to cytochromes of other syntrophic sulfate-reducing partner bacteria. ANME-1c might associate specifically to Thermodesulfobacteria but their co-occurrence is so far restricted to hydrothermal sediments of the Gulf of California. However, in the deep ocean subsurface, sulfate-methane interphases appear at temperatures up to 80 °C, suggesting these as potential habitats for ANME-1c and Thermodesulfobacteria.